ASPECTS RELATED TO THE CONDUCT OF THE PHYSICAL EDUCATION CLASS IN PRIMARY SCHOOL - Dana Ioana CRISTEA; Anca Maria SABĂU (Editura Universităţii din Oradea, 2017)
Physical education, a subject included in the core curriculum in all educational cycles, with different number of hours, aims at training students attitudes and habits, specific to its field, also targeting other areas of education.The current pre-university education in Romania, including the physical education classes, joined the European standards of education.These require further reforms in both the organizational documents and the deployment methodology in the educational process in all university institutions.It is known that physical education lessons are conducted in dedicated facilities (sports court, gyms) but what solution is there when we do not have these spaces?The classroom remains a loophole rescue, a space to be exploited with more creativity and motivation.This paper proposes a series of teaching strategies to achieve the objectives of physical education in primary school.